THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING SKILL OF THE TENTH GRADE STUDENT OF SMK RATNA WARTHA UBUD IN ACADEMIC YEAR 2021/2022 - I Nyoman Juni Artawan Putra; Putu Ayu Paramita Dharmayanti; Ni Luh Putu Dian Sawitri (Academic Journal on English Studies (AJOES), 2022)
This correlational study is aimed to find out the correlation between grammar mastery and writing skill of the tenth grade of SMK Ratna Wartha Ubud in academic year 2021/2022. The samples which were involved in this research were 60 samples selected by using a random sampling method. The researcher used two tests to get the data of grammar mastery and writing skill, such as: multiple choice test items for the grammar mastery and asking students to create descriptive text based on the guiding instrument given. The obtained data were assessed by using SPSS 26.00 version for windows. Based on the data analysis, it showed that there is a high, significant, and positive correlation between grammar mastery and writing skill of the tenth grade students of SMK Ratna Wartha Ubud in academic year 2021/2022. Therefore, the research question was answered that there is a significant correlation between grammar mastery and writing skill.